The Relevance of Sayyid Qutb’s ‘Tafsir fi Zilal al-Quran’ in the Modern Context - Muhammed Afsal Thekkuveettil (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
Sayyid Qutb’s Tafsir fi Zilal al-Quran remains one of the most influential works in modern Islamic thought. Written in the mid-20th century, this exegesis of the Quran addresses not only spiritual guidance but also the socio-political challenges Muslims face in the modern world. Qutb’s interpretation calls for a return to Islamic values, presenting Islam as a comprehensive way of life that addresses justice, governance, and societal ethics. In a world increasingly shaped by secularism, globalization, and Western ideals, Qutb critiques Western influence and champions the establishment of an Islamic state guided by Sharia. His emphasis on social justice, moral responsibility, and rejecting materialism resonates with contemporary debates on identity, governance, and societal values within the Muslim world. This study explores the enduring relevance of Qutb’s tafsir in addressing the spiritual, ethical, and political dilemmas of modern times, offering insights into how Islamic principles can guide personal and societal transformation today. By linking faith to action, Qutb’s work inspires Islamic movements and individuals seeking to navigate the complexities of the modern age while remaining true to their religious heritage. This abstract concisely highlights Qutb’s influence and how his work remains relevant in contemporary discussions on Islam and modern challenges.